2005
DOI: 10.1097/01.tp.0000173994.63299.63
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Adding Mycophenolate Mofetil to Tacrolimus for Nephrotoxicity Following Liver Transplantation

Abstract: Mycophenolate mofetil (MMF) has no known nephrotoxicity. This report examines the outcome in patients who received MMF for renal impairment on tacrolimus-based immunosuppression. From 1995 to 1996, twelve liver transplantation (LTx) patients (mean age 54.6 years) with serum creatinine >1.8 mg/dl were included in the study. MMF was introduced and tacrolimus dose was reduced by 30-50%. Each patient was followed for 6 years. Renal function showed improvement in seven patients, deterioration in four, and no change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 15 publications
2
25
0
3
Order By: Relevance
“…Adding MMF plus subsequent CNI taper were shown to result in renal improvement within a few months [21][22][23][24][25][26][27][28]. Recently, Biselli et al [29] have reported on sustained efficacy and safety of MMF plus low-dose CNI after 2 years.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Adding MMF plus subsequent CNI taper were shown to result in renal improvement within a few months [21][22][23][24][25][26][27][28]. Recently, Biselli et al [29] have reported on sustained efficacy and safety of MMF plus low-dose CNI after 2 years.…”
Section: Discussionmentioning
confidence: 94%
“…The introduction of MMF followed by a significant CNI dose reduction may, however, result in early renal function improvement without increasing the immunological risk for the patient [21][22][23][24][25][26][27]. The long-term impact of this immunosuppressive protocol on renal function and outcome has not yet been analyzed.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Various immunosuppressive approaches have been cited with use of antibody preparation in group of patient with pre-existing renal dysfunction including IL-2 inhibitors and Thymoglobulin [4]. We have in the past published the use of intravenous MMF instead of oral MMF in immediate post-operative period without antibody induction, both to reduce the rate of ACR and preserve renal function [5][6][7]. The rationale for I.V.…”
Section: Renal Functionmentioning
confidence: 99%
“…This drug is far more expensive than the CNIs. Use of MMF has been shown to reduce the requirement of CNI drugs, a definite advantage in patients with a low glomerular filtration rate [5]. Such 'nephroprotection' is particularly required in sick patients with an elevated baseline creatinine.…”
mentioning
confidence: 99%